2017
DOI: 10.1186/s12917-017-1068-6
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of Persistent Müllerian duct syndrome and testicular tumors in dogs

Abstract: BackgroundPersistent Müllerian duct syndrome (PMDS), a rare form of male pseudohermaphroditism in dogs, is an abnormal sexual phenotype in males that is characterized by the existence of a hypoplastic oviduct, uterus, and cranial part of the vagina. Dogs suffering from PMDS are often accompanied by cryptorchidism. To date, it has been mainly found in the Miniature Schnauzer breed.Case presentationIn this report, two cases of PMDS with a malignant testicular tumor originating from cryptorchidism in breeds other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
10
0
7
Order By: Relevance
“…As reviewed previously (Romagnoli, 1991), cryptorchid dogs have a greater risk for testicular neoplasia (especially Sertoli cell tumour and seminoma) and torsion. The association of cryptorchidism with these testicular disorders has been further confirmed in more recent case reports (Bosschere & Deprest, 2010;Bufalari, Proni, Moretti, Di, & A., & Pirico, S., 2015;Hecht, King, Tidwell, & Gorman, 2004;Hong, Lee, Han, & Kim, 2011;Kang et al, 2011;Mostachio et al, 2007;Park et al, 2017;Quartuccio, Marino, Garufi, Cristarella, & Zanghì, 2012;Saegusa et al, 2011;Stokowski, Ruth, Lanz, & Ziglioli, 2016;Withers, Lawson, Burton, Rebhun, & Steffey, 2016) and a retrospective study on canine testicular tumours (Liao, Chu, Yeh, Lin, & Liu, 2009) Spermatic cord torsion was reported in the left neoplastic testis of an 11-year-old bilateral cryptorchid Poodle with left hindlimb lameness as the presenting complaint (Bufalari et al, 2015). It was reported that the lameness resolved completely within 2 days of bilateral cryptorchidectomy.…”
Section: Isorder S a Sso Ciated With Cryp Torchidis Mmentioning
confidence: 56%
See 2 more Smart Citations
“…As reviewed previously (Romagnoli, 1991), cryptorchid dogs have a greater risk for testicular neoplasia (especially Sertoli cell tumour and seminoma) and torsion. The association of cryptorchidism with these testicular disorders has been further confirmed in more recent case reports (Bosschere & Deprest, 2010;Bufalari, Proni, Moretti, Di, & A., & Pirico, S., 2015;Hecht, King, Tidwell, & Gorman, 2004;Hong, Lee, Han, & Kim, 2011;Kang et al, 2011;Mostachio et al, 2007;Park et al, 2017;Quartuccio, Marino, Garufi, Cristarella, & Zanghì, 2012;Saegusa et al, 2011;Stokowski, Ruth, Lanz, & Ziglioli, 2016;Withers, Lawson, Burton, Rebhun, & Steffey, 2016) and a retrospective study on canine testicular tumours (Liao, Chu, Yeh, Lin, & Liu, 2009) Spermatic cord torsion was reported in the left neoplastic testis of an 11-year-old bilateral cryptorchid Poodle with left hindlimb lameness as the presenting complaint (Bufalari et al, 2015). It was reported that the lameness resolved completely within 2 days of bilateral cryptorchidectomy.…”
Section: Isorder S a Sso Ciated With Cryp Torchidis Mmentioning
confidence: 56%
“…As reviewed previously (Romagnoli, ), cryptorchid dogs have a greater risk for testicular neoplasia (especially Sertoli cell tumour and seminoma) and torsion. The association of cryptorchidism with these testicular disorders has been further confirmed in more recent case reports (Bosschere & Deprest, ; Bufalari, Proni, Moretti, Di, & A., & Pirico, S., ; Hecht, King, Tidwell, & Gorman, ; Hong, Lee, Han, & Kim, ; Kang et al, ; Mostachio et al, ; Park et al, ; Quartuccio, Marino, Garufi, Cristarella, & Zanghì, ; Saegusa et al, ; Stokowski, Ruth, Lanz, & Ziglioli, ; Withers, Lawson, Burton, Rebhun, & Steffey, ) and a retrospective study on canine testicular tumours (Liao, Chu, Yeh, Lin, & Liu, ). The retrospective study involved a total of 476 male canine tumours, of which 96 were testicular tumours [33 seminomas ( SEM ), 25 interstitial cell tumours (ICT), 22 were mixed germ cell‐sex cord stromal cell tumours (MGCSCT), and 16 were Sertoli cell tumours (SCT)].…”
Section: Disorders Associated With Cryptorchidismmentioning
confidence: 60%
See 1 more Smart Citation
“…In the veterinary medicine literature, a primary tumor of the uterus masculinus has never been reported (1,7,(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…12 Common sequelae to cryptorchidism in all species is infertility 18 and neoplasia. 15,16,[19][20][21][22][23] However, neoplasia was not identified in the pigs of the present report because of their relatively young age.…”
Section: Commentsmentioning
confidence: 99%